Master your metabolism the 3 diet secrets to naturally balancing your hormones for a hot and healthy body! - Michaels, Jillian; Aalst, Mariska van. (New York : Crown Publishers, 2009)
Health and wellness expert and bestselling author Michaels reveals a simple, three-phase plan to help readers rev up their metabolism by engaging the proper weight-loss hormones.
Includes bibliographical references (pages 202-228)
Keywords: Weight loss -- Endocrine aspects; Metabolism -- Regulation; Electronic books